GAMBARAN KUALITAS HIDUP PASIEN PPOK STABIL DI POLI PARU RSUD ARIFIN ACHMAD PROVINSI RIAU DENGAN MENGGUNAKAN KUESIONER SGRQ - Muthmainnah "; Tuti Restuastuti; Sri Melati Munir (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTChronic Obstructive Pulmonary Disease (COPD) is one of disease that have high morbidity and mortality, even in developingor developed country. One of negative effect of COPD is becoming low in quality of patients’ life because this disease has a chronic and irreversible characters. This research was conducted to know about quality of COPD patients’ life at Poli Paru RSUD Arifin Ahmad of Riau Province, included about patients’ characteristic based on age, sex, occupation, education level, smoking status, and diagnosis level of COPD patients. This research was conducted at Poli Paru RSUD Arifin Ahmad of Riau Province, and the design of this research used cross sectional descriptive design. The sample of this research was COPD patients that has fully achieved of inclusion and exclusion criteria by using collecting consecutive sampling technique with 64 respondents. The data was collected from SGRQ questionnaire. Based on the analyzing of data, there were found that majority of COPD patients contributed onsex (male) (80,28%), elderly (64,78%), primary educational level (36,61%), smoker (61,97%), retired (25,35%), and new COPD diagnostic <3 years (60.56%). In general, the quality of COPD patients’ life is not good which showed (61,97%).Key word: COPD, the quality of life, SGRQ questionnaire